LC-MS/MS-based metabolomics approach identified novel antioxidant flavonoids associated with drought tolerance in citrus species - Rao, Muhammad Junaid; Feng, Bihong; Ahmad, Muhammad Husnain; Tahir ul Qamar, Muhammad; Aslam, Muhammad Zeshan; Khalid, Muhammad Fasih; Hussain, Sajjad; Zhong, Ruimin; Ali, Qurban; Xu, Qiang; Ma, Chongjian; Wang, Lingqiang (Frontiers in Plant Science, 2023)
Citrus fruits are cultivated around the world, and they face drought stress frequently during their growth and development. Previous studies showed that citrus plants biosynthesized flavonoid compounds in response to abiotic stress. In this study, we have quantified 37 flavonoid compounds from the leaves of three distinct citrus species including sour orange (drought-tolerant), pummelo ‘Majia you pummelo’ (drought-sensitive), and lemon (drought-sensitive). The 37 flavonoids consisted of 12 flavones, 10 flavonols, 6 flavanones, 5 isoflavanones, and 1 each for chalcone, flavanol, flavanonol, and flavone glycoside. Drought stress differentially altered the flavonoid metabolism in drought-tolerant and drought-sensitive citrus species. The kaempferol 3-neohesperidoside was 17-fold higher in sour orange (124.41 nmol/L) after 18 days of drought stress than lemon (7.33 nmol/L). In sour orange, neohesperidin (69.49 nmol/L) was 1,407- and 37-fold higher than pummelo and lemon, respectively. In sour orange, some flavonoids were significantly increased, such as vitexin, neohesperidin, cynaroside, hyperoside, genistin, kaempferol 3-neohesperidoside, eriocitrin, and luteolin, in response to drought stress, whereas in lemon, these flavonoids were significantly decreased or not altered significantly in response to drought stress. Moreover, the total contents of flavonoids and antioxidant activity were increased in sour orange as compared with pummelo and lemon. The genes associated with flavonoid biosynthesis (PAL, CHI, FLS, GT1, F3H, F3’M, C4H, 4CL, FLS, FG2, FG3, and CYP81E1) were more highly expressed in sour orange leaves than in pummelo and lemon after drought stress. These outcomes showed that pummelo and lemon failed to biosynthesize antioxidant flavonoids to cope with the prolonged drought stress, whereas the sour orange biosynthesized fortified flavonoid compounds with increased antioxidant activity to detoxify the harmful effects of reactive oxygen species produced during drought stress.